2008
DOI: 10.1007/s12012-008-9024-0
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Type 2 Diabetes and Hypertension in Uygur and Kazak Populations

Abstract: This study was designed to evaluate the epidemiology of type 2 diabetes and hypertension in Uygur and Kazak ethnic populations. A three-step stratified sampling method was used. Questionnaires, blood pressure, anthropometric measurement, and fasting blood glucose were monitored. In total, 1,571 Uygur and 2,913 Kazak subjects were randomly enrolled. The prevalence of type 2 diabetes and glucose intolerance was 5.55-and 1.90-fold higher, respectively, in Uygur than in the Kazak population (8.16 vs. 1.47%, P \ 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 7 publications
2
29
0
Order By: Relevance
“…Some studies indicated that sex hormone level was an independent risk factor for dyslipidemia [27]. Third, The overall prevalence of diabetes was generally low (1.56%) in this study, which was similar with previous Kazakh reports (1.47-3.65%) [28,29], but much lower than 9.7% of the national average level [30]. Unlike previous studies, which reported that diabetes tended to be bundled with hypertension, and that there was substantial overlap between diabetes mellitus and hypertension in etiology and disease mechanisms, our results revealed that diabetes mellitus was a relatively independent disease, and 3.1% of hypertension patients had a coinstantaneous type 2 diabetes mellitus.…”
Section: Epidemic Of Cardiovascular Risk Factorssupporting
confidence: 90%
“…Some studies indicated that sex hormone level was an independent risk factor for dyslipidemia [27]. Third, The overall prevalence of diabetes was generally low (1.56%) in this study, which was similar with previous Kazakh reports (1.47-3.65%) [28,29], but much lower than 9.7% of the national average level [30]. Unlike previous studies, which reported that diabetes tended to be bundled with hypertension, and that there was substantial overlap between diabetes mellitus and hypertension in etiology and disease mechanisms, our results revealed that diabetes mellitus was a relatively independent disease, and 3.1% of hypertension patients had a coinstantaneous type 2 diabetes mellitus.…”
Section: Epidemic Of Cardiovascular Risk Factorssupporting
confidence: 90%
“…In a previous study, we reported that the prevalence of adult diabetes in the Xinjiang Uygur population of western China was 6.23% (Yang et al, 2012). Tao et al (2008) reported that the prevalence of diabetes was 8.16% in the Uygur population and was 1.47% in the Kazak population in 2008, whereas Awuti et al (2012) reported a diabetes prevalence of 9.0% in the Uygur population in 2010. Fu et al (2007) found that the prevalence of diabetes in Chinese children and adolescents was 0.19%, and Cao et al (2007) found total age-adjusted prevalence rates of diabetes and IFG of 0.57 and 1.35% in Beijing children.…”
Section: Introductionmentioning
confidence: 90%
“…The rate of T2DM in the Kazakh population in China is much lower than in the Han population in this region, despite the significant incidence of obesity, insulin resistance, and other risk factors in the Kazakh population (Tao et al, 2008). Therefore, we investigated the contribution of KCNQ1 to the etiology of T2DM in the Chinese Kazakh population to determine whether variants of KCNQ1 were associated with susceptibility to T2DM and diabetes-related metabolic traits.…”
Section: Introductionmentioning
confidence: 99%